FUDECO, the innovative Development Agency of the Central West of Venezuela (Revista Científica Compendium, 2023)
The article characterizes the Foundation for the Development of the Central Western Region of Venezuela (FUDECO) duringthe period 1984-1994 and it is circumscribed to the interest of researchers and territorial actors in the study of development and innovation agencies as key organizations in order to achieve sustainable development. It constitutes a qualitative research of a mixed type: it combines the narrative design of the institutional life history with the study of cases based on publications of the same organization. The analysis reveals that innovation in FUDECO was materialized in the periodic updating of itsorganizational processes and in the conception of its products and services, meeting perceived needs, territorial objectives andavailable resources, based on a strong culture of participation, teamwork, monitoring of the environment and inter-institutional relations. It is concluded that FUDECO assumed innovation as a way of being and doing, behaving as an innovative development agency, a reference for the design or reorganization of territorial organizations.
Keywords: regional development; development and innovation agencies; FUDECO